EDUKASI PERAWAT RUANG RAWAT INAP TENTANG PENGGUNAAN APAR (ALAT PEMADAM API RINGAN) DENGAN TERJADINYA RESIKO BENCANA KEBAKARAN DI RUMAH SAKIT UMUM SEMBIRING DELI TUA - Evfy Septriani Ginting; Armanda Prima; Ripai Siregar; Muhraza Siddiq; Usaha Tarigan (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Hospitals are one of the multi-storey buildings that have a risk of fire, which can come from various sources such as electricity, stoves, as well as storage of flammable materials, such as fuel and medical gas, and power generation facilities such as generators which can cause fires. The aim of this service program is to implement fire prevention measures at the Sembiring General Hospital by holding education sessions for nurses who work there about the use of APAR (Light Fire Extinguisher). Thus, it is hoped that the results of this counseling will be that nurses at Sembiring General Hospital can be effective in using APAR, prevent fires, and have a good understanding of how to save themselves and patients when a fire occurs.